2015
DOI: 10.1093/mnras/stv1298
|View full text |Cite
|
Sign up to set email alerts
|

A transition mass in the local Tully–Fisher relation

Abstract: We study the stellar mass Tully-Fisher relation (TFR; stellar mass versus rotation velocity) for a morphologically blind selection of emission line galaxies in the field at redshifts 0.1 < z < 0.375. Kinematics (σ g , V rot ) are measured from emission lines in Keck/DEIMOS spectra and quantitative morphology is measured from V-and Iband Hubble images. We find a transition stellar mass in the TFR, log M * = 9.5 M . Above this mass, nearly all galaxies are rotation-dominated, on average more morphologically disk… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
76
6

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(95 citation statements)
references
References 100 publications
13
76
6
Order By: Relevance
“…Fig 8 shows our TFR in comparison with those from Green et al (2013) and Simons et al (2015) and our linear fit from Fig. 3 in comparison to that from Reyes et al (2011).…”
Section: D Spatially Resolved Tfrmentioning
confidence: 99%
See 1 more Smart Citation
“…Fig 8 shows our TFR in comparison with those from Green et al (2013) and Simons et al (2015) and our linear fit from Fig. 3 in comparison to that from Reyes et al (2011).…”
Section: D Spatially Resolved Tfrmentioning
confidence: 99%
“…There have been extensive TFR studies with single slit and fibre measurements [Tully & Fisher (1977), Courteau (1997), Böhm et al (2004), Mocz et al (2012) and others]. Despite the success of fibre and slit-based measurements in determining the TFR, they are vulnerable to potential errors introduced by slit placement (Spekkens et al 2005;Oh et al 2011;Simons et al 2015) and aperture effects. It is also difficult to investigate spatial variation across an extended source using a single slit.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, low-mass galaxies are thought to have highly stochastic and bursty SFRs (for example, Gerola et al 1980;Stinson et al 2007;McQuinn et al 2010;Weisz et al 2011;González-Samaniego et al 2014), which in turn can have significant effects on these galaxies' dynamical and morphological evolution. For instance, bursty star formation may explain the lack of coherent, rotationally supported disks in galaxies with M star 10 9.5 M e Muratov et al 2015;Simons et al 2015) and the fact that starforming galaxies are more likely to be dispersion-supported at low mass than at high mass (Roychowdhury et al 2010;Sánchez-Janssen et al 2010;Teyssier et al 2013;Wheeler et al 2015). Many studies have shown that stellar feedback-driven gas outflows can displace a significant fraction of a galaxy's total gas mass (for example, Mathews & Baker 1971;Haehnelt 1995;Christensen et al 2015;Muratov et al 2015), and several recent works have investigated how the resulting time-varying potential can transfer orbital energy to dark matter.…”
Section: Introductionmentioning
confidence: 99%
“…Locally: the majority of high mass galaxies are ordered rotating disks, with kinematically disordered galaxies appearing only below a stellar mass of log M * /M < 9.5 (Simons et al 2015). However, it is unclear whether the kinematic downsizing picture extends beyond z ∼ 1.2 and into the peak of cosmic star-formation.…”
Section: Introductionmentioning
confidence: 99%